A comparative systematic review of Yasmin (drospirenone pill) versus standard treatment options for symptoms of polycystic ovary syndrome. (March 2017) - Li, Jing; Ren, Jing; Sun, Wenxia
Abstract: Objectives: To systematically review the impact of Yasmin (drospirenone pill) compares with other standard treatments for symptoms of Polycystic Ovary Syndrome (PCOS). Study design: The relevant studies of the randomized controlled trials in women with PCOS treated with drospirenone were retrieved and the systematic evaluation was conducted. Results: Eighteen articles were included. Compared with drospirenone (DRSP) monotherapy, DRSP plus metformin was better in reducing body mass index (BMI), luteinizing hormone (LH) and low-density lipoprotein cholesterol (LDL-C). Compared with metformin, DRSP was better in modulating serum total testosterone (T), sex hormone-binding globulin (SHBG), follicle stimulating hormone (FSH) and free androgen index (FAI), while metformin was more effective in reducing BMI, total cholesterol (TC), LDL-C and Triglyceride (TG). DRSP was superior to cyproterone acetate (CPA) in reducing TC and homeostasis model assessment of insulin resistance (HOMA-IR). DRSP shows better effect in modulating LDL-C and high-density lipoprotein cholesterol (HDL-C) compared with desogestrel (DSG). Conclusions: The available data suggested that DRSP was effective in modulating hormones, insulin and lipid metabolism in women with PCOS. Compared with commonly used drugs for symptoms of PCOS as CPA and DSG, DRSP shows identical or better effect in improving symptoms and protect cardiovascular system. For the PCOS patients with IR, obesity or high LH/FSH ratio, DRSP combines with metformin maybe more effective than use DRSP alone.